2015
DOI: 10.1007/s11695-015-1741-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bariatric Surgery on the Saliva of Patients with Morbid Obesity

Abstract: The results suggest that the salivary levels of mutans streptococci increase following bariatric surgery in morbidly obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 19 publications
0
21
0
7
Order By: Relevance
“…The impairment in salivary buffer capacity may lead to a reduced protection of the teeth, which are more susceptible to the development of dental caries and halitosis (1). Although the salivary pH found in this sample of individuals within the normal range of 6.8-7.5 (55,56), the mean pH found in the analysis of buffer capacity may be considered low (57). Considering these findings, a multidisciplinary guidance is a paramount for individuals with morbid obesity to improve their oral and general health conditions.…”
Section: Discussionmentioning
confidence: 93%
“…The impairment in salivary buffer capacity may lead to a reduced protection of the teeth, which are more susceptible to the development of dental caries and halitosis (1). Although the salivary pH found in this sample of individuals within the normal range of 6.8-7.5 (55,56), the mean pH found in the analysis of buffer capacity may be considered low (57). Considering these findings, a multidisciplinary guidance is a paramount for individuals with morbid obesity to improve their oral and general health conditions.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast to the gut microbiome, the salivary microbiome is likely not directly affected by the bariatric surgery, but its composition can be altered indirectly—salivary glucose decreases with body weight loss in diabetic patients with obesity which could enhance growth of bacterial species that prefer a less acidic oral environment 8 , 30 . The post-surgery period is characterized by an increased frequency of meals throughout 31 , which can result in an increase of pathogenic bacteria in the oral cavity, if effective oral hygiene is not practiced 32 . Another factor which might influence salivary microbiome composition is the gastroesophageal reflux.…”
Section: Discussionmentioning
confidence: 99%
“…They detected high C. albicans levels both before and after the intervention and elevated S. mutans levels 6 months after bariatric surgery. However, they also reported that the patients with obesity in their study suffered from a number of chronic systemic comorbidities such as diabetes, for which they were treated with various medications and were prosthesis users, all of which predispose to the expansion of C. albicans [12]. None of these predisposing factors was present in our study, yet in addition to C. albicans, non-albicans Candida species such as C. dubliniensis, C. kefyr, and C. lusitaniae emerged after surgery.…”
Section: Discussionmentioning
confidence: 99%